2003
DOI: 10.1590/s0103-97332003000400007
|View full text |Cite
|
Sign up to set email alerts
|

Gap symmetry of superconducting borocarbide YNi2B2C and skutterudite PrOs4Sb12

Abstract: Within the quasiclassical approximation we have studied the thermodynamics and the thermal conductivity in the vortex state in nodal superconductors (sc). Recent angle dependent magnetothermal conductivity results indicate a gap function ∆(k) corresponding to f-wave sc in Sr 2 RuO 4 and d-wave sc in CeCoIn 5 and κ-(ET)2Cu(NCS)2 respectively. More recently it is shown that ∆(k) in both YNi2B2C and PrOs4Sb12 have point nodes described by hybrid s+g wave gap function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

2004
2004
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…Then the quasiparticle density of states and k zz of A phase is practically the same as in YNi 2 B 2 C: For B phase, on the other hand both of them are proportional to ð1 À sin 2 y sin 2 fÞ 1=2 : These angular dependencies are consistent with data from PrOs 4 Sb 12 [7]. Also as in YN π /4 π /2 3 π /4 π ϕ θ = π /4 θ = π /3 θ = π /2 I(θ,ϕ) …”
supporting
confidence: 84%
“…Then the quasiparticle density of states and k zz of A phase is practically the same as in YNi 2 B 2 C: For B phase, on the other hand both of them are proportional to ð1 À sin 2 y sin 2 fÞ 1=2 : These angular dependencies are consistent with data from PrOs 4 Sb 12 [7]. Also as in YN π /4 π /2 3 π /4 π ϕ θ = π /4 θ = π /3 θ = π /2 I(θ,ϕ) …”
supporting
confidence: 84%
“…Also solving Eq. (4) for G=D > 1; we can show DðT; GÞ obeys the same gap equation as the one for s-wave superconductor with the transition temperature T c : More details have been reported elsewhere [10][11][12]. …”
supporting
confidence: 71%
“…12 Theoretical studies of nonmagnetic impurity scattering in anisotropic superconductors indicate that this type of disorder has much more profound effects on the hybrid sϩg-wave superconductors with point nodes than on other unconventional superconductors with line nodes. 13,14 In particular, it was observed that the unitary limit and the weakscattering Born limit give practically the same results over a wide range of parameters. Also, contrary to superconductors with line nodes, no low-frequency resonance is found for the strong-scattering case.…”
Section: Introductionmentioning
confidence: 78%
“…This dependence is well approximated by g ϭ⌫/(1ϩ2⌫/⌬). 13,14 Typical quasiparticle densities of states for the pure sϩg-wave system and in the presence of impurity scattering are shown in Fig. 1͑b͒.…”
Section: Introductionmentioning
confidence: 99%